Hypophysitis secondary to nivolumab and pembrolizumab is a clinical entity distinct from ipilimumab-associated hypophysitis. Issue 3 (September 2019) - Faje, Alexander; Reynolds, Kerry; Zubiri, Leyre; Lawrence, Donald; Cohen, Justine V; Sullivan, Ryan J; Nachtigall, Lisa; Tritos, Nicholas
Abstract : Objective: Little has been published describing hypophysitis after nivolumab or pembrolizumab treatment. We aimed to (i) assess the risk of hypophysitis following nivolumab or pembrolizumab treatment, (ii) characterize the clinical presentation and outcomes in these patients and (iii) compare these patients to hypophysitis following ipilimumab and ipilimumab plus nivolumab (combo). We hypothesized that headaches, pituitary enlargement on MRI and multiple anterior pituitary hormone deficiencies would occur less often in the nivolumab/pembrolizumab group versus ipilimumab or combo hypophysitis patients. Design and methods: We conducted a multi-center retrospective review utilizing the Research Patient Database registry to evaluate individuals diagnosed with hypophysitis following treatment with nivolumab/pembrolizumab ( n  = 22), ipilimumab ( n  = 64) and combo ( n  = 20). Encounter notes, radiologic imaging and laboratory results for these patients were comprehensively reviewed. Results: Hypophysitis was rare following treatment with nivolumab/pembrolizumab (0.5%, 17/3522) compared to ipilimumab (13.6%, 34/250), P  < 0.0001. Hypophysitis was diagnosed later in nivolumab/pembrolizumab (median: 25.8 weeks, interquartile range (IR): 18.4–44.0) compared to ipilimumab (9.3, IR: 7.2–11.1) or combo patients (12.5, IR: 7.4–18.6), P  < 0.0001 for both. Headache and pituitary enlargement occurred less commonly in nivolumab/pemrolizumab patients (23% and 5/18, respectively) compared to ipilimumab (75%, 60/61) and combo (75%, 16/17) treatment groups ( P  < 0.0001 versus ipilimumab and P  = 0.001 versus combo for headache and P  < 0.0001 for both for enlargement). Conclusions: This study represents the first comprehensive cohort analysis of nivolumab or pembrolizumab-associated hypophysitis in a large patient group. Hypophysitis occurs rarely with these medications, and these patients have a distinct phenotype compared to hypophysitis after treatment with ipilimumab or ipilimumab plus nivolumab.